2017
DOI: 10.1073/pnas.1619583114
|View full text |Cite
|
Sign up to set email alerts
|

Accurate age estimation in small-scale societies

Abstract: Precise estimation of age is essential in evolutionary anthropology, especially to infer population age structures and understand the evolution of human life history diversity. However, in small-scale societies, such as hunter-gatherer populations, time is often not referred to in calendar years, and accurate age estimation remains a challenge. We address this issue by proposing a Bayesian approach that accounts for age uncertainty inherent to fieldwork data. We developed a Gibbs sampling Markov chain Monte Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 14 publications
0
42
0
Order By: Relevance
“…To estimate age, we took the mean values from posterior probability distributions of age produced using a Gibbs sampling MCMC algorithm based on age ranking order data provided by the Agta and a plausible a priori age range for each individual provided by the ethnographers 36 .…”
Section: Data Collectionmentioning
confidence: 99%
“…To estimate age, we took the mean values from posterior probability distributions of age produced using a Gibbs sampling MCMC algorithm based on age ranking order data provided by the Agta and a plausible a priori age range for each individual provided by the ethnographers 36 .…”
Section: Data Collectionmentioning
confidence: 99%
“…Moreover, to help attenuate sample size concerns, we collected repeated samples across participants and also used data analytical techniques that maximized the information from these repeated observations. www.nature.com/scientificreports/ In addition, the BaYaka do not record their calendar ages, thus we estimated an approximate age based on a procedure from Diekmann and colleagues and with their assistance 84 . In validating their method, Diekmann et al found the calculations were reliable within a year of known ages (median: 4 months; mean: 11 months) for another forager society, giving us confidence in the BaYaka calculated ages 84 .…”
Section: Discussionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ In addition, the BaYaka do not record their calendar ages, thus we estimated an approximate age based on a procedure from Diekmann and colleagues and with their assistance 84 . In validating their method, Diekmann et al found the calculations were reliable within a year of known ages (median: 4 months; mean: 11 months) for another forager society, giving us confidence in the BaYaka calculated ages 84 . Still, because of inter-correlations between BaYaka age, T, and fathering rankings, the reliability of these age calculations could be potentially concerning in terms of adjusting our models for age.…”
Section: Discussionmentioning
confidence: 99%
“…Except for Early and Headland's work (7) on the Agta, in which the ages of 271 of the 857 individuals (31.6%) were known (117 individuals to within a year, 80 to within a month, and 74 exactly to the day; see table 4.1 in ref. 7), authors have had to develop various methods to estimate the missing chronological information (15). From data provided by many scholars, Weiss (16) built model life tables to infer, from a limited number of variables, many demographic/life-history parameters, such as life expectancy or the ASFR for each 5-y age cohort.…”
Section: Overview: Moange Le Bosquetmentioning
confidence: 99%